Cover Image. Issue 5 (19th October 2020) - Unknown
Abstract : Pratick Samanta and coworkers describe the preparation of poly (L‐lactic acid) (PLLA) hollow nanofiber bundles through anodic aluminum oxide (AAO) membrane wetting technique in the article e10147. Preserving its original nanostructure, individual hollow nanofiber was isolated via selective etching of the AAO membrane using phosphoric acid. The confined crystallization behavior of these hollow nanofibers inside the AAO pores is discussed. The image shows the top view SEM image of the PLLA nanofibers bundles after selective etching of AAO membrane. (doi.org/10.1002/pcr2.10147 ) Abstract : Pratick Samanta and coworkers describe the preparation of poly (L‐lactic acid) (PLLA) hollow nanofiber bundles through anodic aluminum oxide (AAO) membrane wetting technique in the article e10147. Preserving its original nanostructure, individual hollow nanofiber was isolated via selective etching of the AAO membrane using phosphoric acid. The confined crystallization behavior of these hollow nanofibers inside the AAO pores is discussed. The image shows the top view SEM image of the PLLA nanofibers bundles after selective etching of AAO membrane. (doi.org/10.1002/pcr2.10147 )